Environmental and Social Management System Toolkit and Case Studies : Food and Beverage - International Finance Corporation (Washington, DC, 2014)
Environmental and social responsibility is becoming more and more important in today's global economy. There are thousands of environmental and social codes and standards in the world today. The codes and standards define the rules and the objectives. But the challenge is in the implementation. An environmental and social management system helps companies to integrate the rules and objectives into core business operations, through a set of clearly defined, repeatable processes. This handbook provides tools to build or enhance a company's environmental and social management system (ESMS). Section I is the Toolkit - sample documents, blank forms, flowcharts, checklists and templates. There are tools for each of the nine elements in the ESMS. Section II is the Case Studies - examples of how two different companies used the tools and developed and implemented an ESMS appropriate to the size and nature of their business.